ANALISIS PEMASARAN CENGKEH DI DESA JONO OGE KECAMATAN SIRENJA KABUPATEN DONGGALA - Lisnawati Lisnawati; Hadayani Hadayani; Yulianti Kalaba (Universitas Tadulako, 2017)
This study aimed to determine marketing channels, to identify marketing marginand marketing efficiency of cloves to determinethe portionof clove prices received by farmers in JonoOge village of Sirenja district. The population in this study was all farmers (107 people) who run farming cloves and traders involved in the marketing of cloves. The number of respondents included was 43 farmers and 7 collectors. Data was analyzed using analysis of marketing margins, marketing efficiency and price portions received by farmers. The marketing analysis results showed that there were three marketing channels: (I) Farmers – Village Collector –Sub District Collector – Inter-island Trader; (II) Farmers –Sub District Collector – Inter-island trader; and (III) Farmers – Inter-island Trader. The marketing margin was USD 7,000 for channel I, USD 5,000for channel II, and USD 3,000 for channel III with the farmer's share price of 94.26%, 95.90% and 97.54%, respectively. The channel marketing efficiency for the three channels was 2.59, 2.23 and 1.37, respectively.